Proof-of-Concept Development of the Distal Module of a Cystoscope Transurethral Continuum Surgical Robotic System - Kuang, Haomin; Wang, Xiang; Zhao, Chen; Zhu, Chuanxiang; Xu, Kai (IEEE robotics and automation letters, 2024)
Transurethral resection of bladder tumor (TURBT) is the typical procedure for non-muscle invasive bladder tumors. However, current TURBT using rigid surgical tools can hardly handle en bloc resection of bladder tumor and anterior tumor resection. This letter hence proposes a teleoperation-based cystoscope transurethral continuum surgical robotic system and conducts proof-of-concept development of its distal module. The distal module uses a parallel continuum robot (PCR) form to fully utilize the urethra cross section as well as realize marker-less visual closed-loop control. The design of the distal module starts with a topology optimization of the PCR. Then, the PCR is modeled and optimized for better structural stiffness. Besides, the use of the PCR can inherently facilitate marker-less visual closed-loop control since its mobile platform has a toroidal shape that is easily identifiable in the endoscopic image based on the contour detection algorithm. The functionality of the distal module is evaluated via the experiments on a proof-of-concept construction. The distal module can grip the bladder mucosa and perform tumor resection with a bipolar loop under teleoperation. The experimental results showed that the 3-DoF (Degree of Freedom) distal module with an outer diameter of 7 mm realized a functional workspace volume of a φ 25-mm sphere and an average position error of 0.40 mm under closed-loop control. The teleoperation with closed-loop and open-loop control transition demonstrates a great potential for en bloc tumor resection.